Aktivitas Kehidupan Malam di Kawasan Jalan Malioboro (Studi Terhadap Pemuda Pengunjung Malioboro Saat Pandemi COVID–19) - Isfan Fajar Sukarno; Rani Noor Vernanda (Universitas Gadjah Mada, 2022)
The COVID-19 pandemic that occurred in Indonesia caused the closure of public spaces as an effort to limit social interaction to prevent transmission. This policy affects the needs of youth for public spaces as a means for them to carry out night activities. For youth, nightlife activities are not just moments to find fun, but also build their identity. Malioboro is one of the places in Yogyakarta that is a destination for youth to do night activities. This research focuses on nightlife activities carried out by youth in Malioboro during the COVID-19 pandemic. In addition, this study seeks to see the need for youth to have space for expression and shape their identity. Based on this focus, this study looked at how a Malioboro Area space can be reproduced by youth through activities at night to meet their needs. This research uses the case study method, whereresearchers conduct an in-depth analysis of a case through and tracing a number of data that is limited in time and place. Based on the findings of field data, it shows that activities at night in Malioboro for youth are a necessity even during a pandemic. They see the Malioboro Area as having an appeal through symbols that are displayed as the identity of the space. So the youth use Malioboro as a place to express according to their wishes in taking advantage of free time at night. Based on these findings, it can be explained that youth and a space are related in the formation of identity.